2020
DOI: 10.1002/slct.201904076
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antiproliferative Evaluation of 5′‐Arylchalcogenyl‐3‐(phenylselanyl‐triazoyl)‐thymidine

Abstract: This article discloses the synthesis and biological in vitro activity of a novel class of compounds derived from 5′‐arylchalcogenyl‐3‐(phenylselanyl‐triazoyl)‐thymidine as antitumor agents in the 5637 bladder carcinoma. The synthesis of the new molecules obtained good yields and proved to be efficient. The antitumor biological property, which was presented by a series of these unpublished compounds, demonstrates the importance of the presence of the nucleoside portion and the chalcogenium atom in the molecule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Previous data from the group have demonstrated that new compounds formed by adding chalcogen atoms to the structure of commercial AZT were able to enhance the in vitro antioxidant and antitumor action of the hydride molecules [ 46 , 47 ]. In this context, it was reported that the presence of chalcogen in the molecule 5′-arylchalcogenyl-3-(phenylselanyl-triazoyl)-thymidine reduced the proliferative capacity of bladder cancer cells and amplified the activity of the compound [ 48 ]. Additional results revealed that in breast cancer cell line, AZT analogs containing tellurium were more effective in inhibiting tumor growth and showed lower cytotoxicity than the original antiretroviral molecule [ 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous data from the group have demonstrated that new compounds formed by adding chalcogen atoms to the structure of commercial AZT were able to enhance the in vitro antioxidant and antitumor action of the hydride molecules [ 46 , 47 ]. In this context, it was reported that the presence of chalcogen in the molecule 5′-arylchalcogenyl-3-(phenylselanyl-triazoyl)-thymidine reduced the proliferative capacity of bladder cancer cells and amplified the activity of the compound [ 48 ]. Additional results revealed that in breast cancer cell line, AZT analogs containing tellurium were more effective in inhibiting tumor growth and showed lower cytotoxicity than the original antiretroviral molecule [ 46 ].…”
Section: Introductionmentioning
confidence: 99%